Predisposing Factors for Sexual Dysfunction in Multiple Sclerosis - Altmann, Patrick; Leutmezer, Fritz; Leithner, Katharina; Monschein, Tobias; Ponleitner, Markus; Stattmann, Miranda; Rommer, Paulus Stefan; Zrzavy, Tobias; Zulehner, Gudrun; Berek, Klaus; Berger, Thomas; Bsteh, Gabriel (Frontiers in Neurology, 2021)
Sexual dysfunction (SD) in people with multiple sclerosis (pwMS) has a detrimental impact on individual health related quality of life (HRQoL). It is not clear whether SD in multiple sclerosis (MS) is an independent symptom or merely a byproduct of other symptoms such as depression or anxiety. This cross-sectional study of 93 pwMS determines risk factors for SD in MS based on prevalence, HRQoL and associated disease outcomes. Diagnosis of SD was determined based on the Multiple Sclerosis Intimacy and Sexuality Questionnaire-19 (MSISQ-19) and correlated with physical disability (measured by Expanded Disability Status scale, EDSS), depression and anxiety (HADS, Hospital Anxiety and Depression Scale), and HRQoL (MSQoL-54, Multiple Sclerosis Quality of Life-54). Multivariate regression models were performed to determine independent risk factors for SD in pwMS. Almost half of participants in this study (46%) reported SD. HRQoL was significantly poorer in patients with MS suffering from SD (median [IQR] MSQoL-54 scores: physical subscale 52 [41-68] vs. 81 [69-89], p<0.001; mental subscale 50 [38-82] vs. 86 [70-89], p<0.001). In the multivariate model, EDSS was the only independent risk factor for SD (OR 18.1 for EDSS≥4 [95%CI 3.3-31.4, p<0.001]), while depression and anxiety were not. We conclude that the risk for SD is growing with increasing EDSS and is independent of depression or anxiety. Screening for SD becomes particularly relevant in patients with growing disability. Keywords: sexuality, sexual dysfunction, multiple sclerosis, risk